Augmentative & alternative communication: supporting children and adults with complex communication needs - Beukelman, David R., 1943-; Light, Janice C. (Janice Catherine) (Baltimore Paulh Brookes, 2020)
"The fifth edition of Augmentative & Alternative Communication: Supporting Children and Adults with Complex Communication Needs is the premier resource for anyone planning to work with individuals who rely on AAC. Written for pre-service and in-service SLPs, OTs, PTs, assistive technicians, and other direct service providers, this book is a comprehensive guide to the characteristics of people with complex communication needs, the variety of AAC systems available, and current assessment and intervention practices in AAC"--
Includes bibliographical references and index.
Keywords: Communicative disorders -- Patients -- Rehabilitation; Communication devices for people with disabilities; Nervous system -- Diseases -- Complications